RUSSIAN–JAPANESE TRADE AND ECONOMIC RELATIONS: IS THERE A NEW FULCRUM? - D. V. Streltsov (Vestnik MGIMO-Universiteta)
Against the background of political chilling between Russia and Japan trade and economic cooperation objectively form a basis for a positive development of bilateral relations in the foreseeable future. The structure of mutual trade has not changed significantly for a number of years. Russia plays the role as a pivotal supplier of certain raw materials for the Japanese market, namely energy resources, non-ferrous metals, seafood and timber. From Japan Russia imports mainly passenger cars and a certain amount of industrial equipment. With regard to investment relations between Russia and Japan, there exists a serious structural problem - the two economies are interdependent from the point of view of the technological division of labor. Russia, particularly its Eastern regions, not possessing sufficient infrastructure and logistics capabilities, as well as cheap labor resources, does not have any competitive advantages for Japanese investment compared to other countries like China. The potential of Russia is mostly viewed in Japan just as an energy donor. Thus the largest prospects of investment cooperation lie in the energy sphere. One can talk of the possibility for raising Russia's share in the Japanese oil and LNG markets. This perspective is supported by the instability of the political situation in the Middle East, which is Japan's main partner for energy supplies. In this connection, large-scale investment projects in the energy field, like the construction of gas pipeline "Sakhalin - Japan" or a power bridge "Sakhalin - Hokkaido", retain their perceptiveness. However, given the political, juridical, organizational, technical and other problems, these projects are difficult for implementation at the present stage. In this situation, the allocation of a certain share for Japan in the strategic energy deposits of Siberia and the Far East and the admission of Japanese capital to the exploration and development of these deposits seem to be a realistic choice for Russian strategic planning towards Japan, as such a cooperation would not be a subject of Western sanctions against Russia. For Russia it is important to build with Japan relationship on a more long-term and lasting basis. One of the possible ways here is to conclude a bilateral economic partnership agreement.